Microfinance and its Impact in Poverty Alleviation in Nigeria: A Case Study of some Microfinance Banks in Edo State. - Imoisi, Anthony; opara, godstime (American Journal of Humanities and Social Sciences, 2014)
This research examines the relationship microfinance and poverty alleviation in Nigeria, to understand the effectiveness of micro credit within the context of its current practice in Edo State in particular, and the nation as a whole as a tool for wealth creation and capital accumulation among the poverty stricken populace and low income earners. The study made use of primary data obtained through field survey from the selected microfinance banks in Edo State and utilized quantitative tools to analyze these data so as to bring out any existing relationship between microfinance and poverty alleviation. The results obtained showed that microfinance has the potential of alleviating poverty by ensuring wealth creation and its attendant self-sufficiency. From our result, about 70% of the sampled population agreed that there is a positive relationship between microfinance and improved standard of living of the recipients of these micro credits; 78% attested that they obtained some sort of credit from microfinance banks to set up their small scale businesses, without which it would be impossible to do so; about 67% said they have used loan collected to expand their business while 24% said they used the loan collected to invest on new technology for their business and the remaining 9% of the respondents obtained loans to facilitate the export of their products. Focus of microfinance programmes in poor communities for it to be meaningful; a massive educational drive on the importance of microfinance in fighting widespread poverty should be launched in the country; etc were some of the recommendations made in this study